(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Through this research paper, I intend to highlight the significance of intercultural competence for foreign language teacher. How a foreign language teacher should be aware of students’ cultural backgrounds and behavioral dynamics to fit him herself in different circumstances. Learning a language opens a new window to a new culture as language and culture are intricately linked to each other.The paper intends to explain how a foreign language teacher should be open-minded and receptive, be able to withhold any biased judgement and know how to treat the students optimally. How can teachers help the students to develop an ’intercultural lens’ to view the world?